The Effect Of Multiple Box Jumps Training On The Height Of Heading Jumps In Extracurricular Football Smpn 12 Kota Bengkulu - Ramadansyah, Disen; Ferdima, Feby Elra; mar, Martiani (Social Sciences Journal, 2025)
This study aims to the effect of multiple box jumps training on the height of heading jumps in extracurricular football at SMPN 12 Bengkulu City. This type of research is quantitative research. The research sample totalled 20 people. The instrument used in this study was a heading test in a football game using multiple box jump treatment. The results of the pretest shotting and posttest heading tests conducted using multiple box jump training obtained rtabel of 0.443 because the correlation coefficient between rxy = 0.93> 0.443 and an influence of 86.20% which means that with the discovery of the effect of multiple box jumps training on the height of heading jumps in extracurricular football SMPN 12 Bengkulu City, then multiple box jump training can be used to measure the height of heading jumps in extracurricular football SMPN 12 Bengkulu City.